Clash of Cultures in Louise Erdrich's books - Čubíková, Monika (Univerzita Pardubice, 2010)
The aim of this work is to illustrate the impact of the arrival of European settlers in the American continent, whose intention was to entirely assimilate Native Americans. The thesis refers to boarding schools as one of the most powerful tool, which the Euro-Americans used to achieve the above mentioned aim. It also depicts other problems Native Americans have had to deal with, such as oppressive financial situation, cultural uprooting, racism, alcoholism, tense family situation and loss of their lands, traditions and tribal languages. These issues are analyzed on the novels of Louise Erdrich, member of the Turtle Mountain Chippewa Band residing in North Dakota.
Střet kultur v knihách Louise Erdrichové
Keywords: Indiáni; Chippewajové; Euro-Američané; tradice; asimilace; závislost na alkoholu; Native Americans; Chippewa; Euro-Americans; traditions; assimilation; alcohol addiction